Synthesis, characterization and adsorption studies of an acrylic acid-grafted sodium alginate-based TiO hydrogel nanocomposite - Sourbh Thakur; Omotayo Arotiba (Adsorption Science & Technology)
Hydrogel nanocomposites were synthesized by solution polymerization of acrylic acid in the presence of sodium alginate biopolymer and TiO 2 nanoparticle. TiO 2 nanoparticle and N , N -methylene-bis-acrylamide was used as an inorganic and organic crosslinker, respectively. The structure and morphology of the nanocomposites were investigated using X-Ray Diffraction (XRD), Fourier Transform Infra-Red Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Brunauer-Emmett-Teller (BET) and thermogravimetric analysis techniques. The nanocomposites hydrogel was used for the adsorption of methyl violet dye from water. The influence of TiO 2 nanoparticle, sodium alginate content and grafting on adsorption were studied. The results showed that a pseudo-second-order adsorption kinetic was predominant in the adsorption of methyl violet onto the nanocomposite hydrogel. The experimental equilibrated adsorption capacity of the nanocomposite hydrogel agrees with Langmuir isotherm. Maximum adsorption capacity of 1156.61 mg g −1 and adsorption efficiency of 99.6% towards methyl violet were obtained for the hydrogel nanocomposite.